2017
DOI: 10.1007/s12520-017-0508-3
|View full text |Cite
|
Sign up to set email alerts
|

Archaeological geophysical survey of a Prehistoric Bronze Age site in Cyprus (Alambra Mouttes)—applications and limitations

Abstract: The University of Queensland Alambra Archaeological Mission (UQAAM) conducted a program of geophysical survey and archaeological excavation over four seasons from 2012 to 2016. This program has allowed this study to compile a large array of geophysical data, which has been tested against actual excavation results. By integrating the two forms of archaeological investigation, the UQAAM has been able to identify geophysical 'signatures' diagnostic and indicative of internal architectural features relating to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…The focus here has been on the north of the island. Elsewhere, there is increasing evidence for workshop production of metal, pottery, textiles, perfume, oils, and perhaps beer [67] (p. 217), [108,[151][152][153][154], suggesting a similar targeted use of the landscape and its resources and a significant degree of mobility in the volume and flow of goods and information within regional and perhaps inter-regional networks. While we may not be able to trace in detail the transformation from egalitarian villages to communities with surplus accumulation (see [155,156]), we can argue for the interdependence of settlements within networks maintained through regular contacts and the movement of people and goods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The focus here has been on the north of the island. Elsewhere, there is increasing evidence for workshop production of metal, pottery, textiles, perfume, oils, and perhaps beer [67] (p. 217), [108,[151][152][153][154], suggesting a similar targeted use of the landscape and its resources and a significant degree of mobility in the volume and flow of goods and information within regional and perhaps inter-regional networks. While we may not be able to trace in detail the transformation from egalitarian villages to communities with surplus accumulation (see [155,156]), we can argue for the interdependence of settlements within networks maintained through regular contacts and the movement of people and goods.…”
Section: Discussionmentioning
confidence: 99%
“…It was occupied already in the Philia EC period, but grew rapidly in the MBA when burial evidence suggests a massive upsurge in population that could not have been achieved by natural increase alone (estimates of the MBA mortuary population range from 9000 to 20,000, see [76]) (pp. [152][153][154]. It is well-positioned to have served as a broker/trans-shipment point both on a north/south route through the Agirdha Pass and east/west along the Ovgos Valley, as well as an agricultural production centre and perhaps an organisational outpost.…”
Section: The Issue Of Centralitymentioning
confidence: 99%
“…It was anticipated that the collection of GPR data may be hindered by the soil of the Troodos region which is known to be clay-rich with substantial rubble inclusions, characteristics also found elsewhere on the island of Cyprus [10][11][12]. There was also known to be significant moisture content due to the presence of clay.…”
Section: Methodsmentioning
confidence: 99%
“…Neustupný suggested that the remains of settlement activities by individual prehistoric communities accumulated within the original 'settlement areas' with various functions [32] (pp. [154][155]. The principles that make community area different to settlement chamber theory is that the former relies mostly on environmental factors (e.g., land fertility, water sources and natural paths) to define settlement chambers, while the latter includes historical and social variables to define community areas [27] (pp.…”
Section: Landscape Archaeology Siedlungskammer and Community Area Theorymentioning
confidence: 99%
“…Thus, landscape is not perceived as "a geographical unit, but the relic of a past social world" [32] (pp. [154][155]. This spatial and temporal 'continuity' in settlements within the same community area (at or beside the occupation of the previous phase, associated with specific environmental qualities and historical variables) does not necessarily denote ethnic or cultural continuity, which may appear or disappear along with material traces of human activity [14] (pp.…”
Section: Landscape Archaeology Siedlungskammer and Community Area Theorymentioning
confidence: 99%